2002
DOI: 10.1093/ejo/24.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric measurements and facial deformities in subjects with  -thalassaemia major

Abstract: This study was performed to identify cephalometric and facial features of patients with beta-thalassaemia major. A total of 54 thalassaemic subjects were examined for craniofacial deformities, including 37 patients (24 males and 13 females, aged 5-16 years) who had lateral cephalometric radiographs. The thalassaemic groups were compared with a normal control group matched for sex and dental age, using a t-test. All thalassaemic patients had a Class II skeletal base relationship. The average ANB angle was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
88
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 14 publications
11
88
0
Order By: Relevance
“…In Qatar, Abu Alhaija et al [5] conducted measurements of the lateral cephalograms of 37 thalassemia patients (24 males and 13 females between 5 and 16 years of age). The thalassemia group patients were found to have a class II skeletal model, and their maxillae were found to be normal in size; meanwhile, the smaller length of the cranial base was suggested to result from the short mandible [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Qatar, Abu Alhaija et al [5] conducted measurements of the lateral cephalograms of 37 thalassemia patients (24 males and 13 females between 5 and 16 years of age). The thalassemia group patients were found to have a class II skeletal model, and their maxillae were found to be normal in size; meanwhile, the smaller length of the cranial base was suggested to result from the short mandible [5].…”
Section: Discussionmentioning
confidence: 99%
“…The thalassemia group patients were found to have a class II skeletal model, and their maxillae were found to be normal in size; meanwhile, the smaller length of the cranial base was suggested to result from the short mandible [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They result primarily from hypertrophy and expansion of the erythroid marrow due to ineffective erythropoiesis (formation of erythrocytes). Orofacial changes in TM have described in earlier reports (4)(5)(6)(7)(8). TM patients are at high risk of dental caries (9,10) periodontal diseases (8,11) and oral infection (5,12).…”
Section: Introductionmentioning
confidence: 90%
“…The typical findings in subjects with thalessemia are a class II skeletal pattern, short cranial base length, short cranial length, short mandible, increased anterior and reduced posterior vertical dimensions and severe facial disfigurement as narrated by Alhaija et al 21 Bone age was delayed in protein energy malabsorption and males were affected more than females in accordance with studies of Tanner et al 22 and Frisancho et al 23 Malnutrition affected the maturation of the skeleton more than the teeth as confirmed by Steward et al 18 and Garn et al 19 According to a recent study conducted by Nathani et al, 24 frontal sinus can also be used as predictor for evaluation of growth patterns. In fact it has been found to be more reliable than maxillary sinus in assessment of different types of malocclusions.…”
Section: Discussionmentioning
confidence: 94%